2010
DOI: 10.1149/1.3266932
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Metal Nanowhiskers on Patterned Substrate by High Temperature Glancing Angle Deposition

Abstract: In this study, we carry out high temperature glancing angle deposition (HT-GLAD) of Fe and Al on a heated substrate with trench patterns. When vapor is incident perpendicular to the trench direction, nanowhiskers grow only on the surface exposed to the vapor and not inside the trenches. When vapor is incident at a deposition angle larger than 80° on the sidewall of the trench and not on the substrate surface, nanowhiskers grow only on the sidewall because the condition of deposition at a high temperature and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…[154][155][156][157][158] For the case of metal nanowires, the substrate temperature should be higher than about one third of the metal's melting point and the deposition angle typically should exceed 80° with regard to the substrate normal. For the VO 2 nanowires in the present study, we expect that the relative magnitude of the fluxes of vanadium atoms and oxygen molecules plays a decisive role.…”
Section: Conclusion and Remarksmentioning
confidence: 99%
“…[154][155][156][157][158] For the case of metal nanowires, the substrate temperature should be higher than about one third of the metal's melting point and the deposition angle typically should exceed 80° with regard to the substrate normal. For the VO 2 nanowires in the present study, we expect that the relative magnitude of the fluxes of vanadium atoms and oxygen molecules plays a decisive role.…”
Section: Conclusion and Remarksmentioning
confidence: 99%
“…To date, Al nanostructures (e.g., 2D nanopatterns and 1D nanowires (NWs), and nanotubes (NTs)) are mainly fabricated by top‐down lithographic methods, including electron beam lithography (EBL), nanosphere lithography (NSL), and anodized aluminum oxide (AAO) template lithography . For bottom‐up, self‐assembled growth, wet chemical methods are restricted to the fabrication of noble metal (e.g., Au, Ag, Pt) nanostructures , though there have been reports of stress‐induced , electromigration‐induced and vapor‐phase growth in glancing angle deposition of Al microwires and nanowires. The advantages of bottom‐up growth of Al nanostructures are ultra‐smoothness and the possibility in formation of 3D structures.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of bottom‐up growth of Al nanostructures are ultra‐smoothness and the possibility in formation of 3D structures. Existing bottom‐up techniques for Al nanostructures are still in the early development stage, requiring improvements in achieving higher yields, controlling growth conditions and reaching smaller dimensions .…”
Section: Introductionmentioning
confidence: 99%
“…For the experimental conditions used in the present study, nanorod structuring on room temperature substrates occurs for materials with melting points higher than that of Al ͑933 K͒. It has been reported that GLAD-grown Al, 30,31 Fe, 31 and Ag 32 films have isolated nanowhiskers on planar morphologies when grown by electron beam evaporation or ion beam deposition at elevated temperatures, but such flat film morphologies containing only a few isolated nanowhiskers do not fall into our definition of a nanorod structured film and thus should not be compared with the film types reported in the present study.…”
Section: Resultsmentioning
confidence: 92%